The determination of frequency domain soil parameters of horizontally layered structure by using dipole‐dipole array. (19th February 2019) - Li, Zhong‐Xin; Rao, Shao‐Wei
Abstract: A method to determine frequency domain soil parameters of horizontally layered structure is developed, including resistivity and permittivity. The theoretical formula of apparent resistivity of dipole‐dipole array is derived from Green's function under quasi‐static field condition. Complex image method is introduced to avoid time‐consuming numerical integration in apparent resistivity calculation, which improves the computational efficiency significantly. The frequency domain soil parameters are optimized using simulated annealing algorithm at each frequency. This method is applied to invert synthetic data with noise and the inversion results validate the accuracy of this method.